C.S. Lewis and a Problem of Evil an Investigation of a Pervasive Theme. - Root, Jerry (Havertown : James Clarke & Co, 2010)
C.S. Lewis was concerned about an aspect of the problem of evil he called subjectivism: the tendency of one's perspective to move towards self-referentialism and utilitarianism. In C.S. Lewis and a Problem of Evil, Jerry Root provides a holistic reading of Lewis by walking the reader through all of Lewis's published work as he argues Lewis's case against subjectivism. Furthermore, the book reveals that Lewis consistently employed fiction to make his case, as virtually all of his villains are portrayed as subjectivists. Lewis's warnings are prophetic; this book is not merely an exposition of.
Front Cover; Title Page; Copyright information; Contents; Acknowledgements; Preface; 1. Objectivity and Evil; 2. The Problem of Pain; 3. Lewis's Literary Criticism and a Problem of Evil; 4. The Rhetorical Aim of Lewis's Fiction in Light of a Problem of Evil; 5. Literary Analysis; 6. Conclusions; Permissions; Bibliography; Back cover.
Print version record.
Includes bibliographical references.
Master record variable field(s) change: 072
Keywords: Lewis, C. S. -- 1898-1963.; Lewis, C. S. -- 1898-1963.; Theodicy; Good and evil -- Religious aspects -- Christianity; Subjectivity -- Religious aspects -- Christianity; Christianity in literature; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Christianity in literature; Good and evil -- Religious aspects -- Christianity; Subjectivity -- Religious aspects -- Christianity; Theodicy; Christianity in literature; Good and evil -- Religious aspects -- Christianity; Lewis, C. S. -- (Clive Staples), -- 1898-1963.; Subjectivity -- Religious aspects -- Christianity; Theodicy; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Electronic books